2007
DOI: 10.1159/000107625
|View full text |Cite
|
Sign up to set email alerts
|

The Practical Reality of Using a Patient-Reported Outcome Measure in a Routine Dermatology Clinic

Abstract: Objective: To explore whether clinicians used formal quality of life (QoL) information if provided by patients completing the Dermatology Life Quality Index (DLQI) questionnaire and whether the information influenced treatment decision-taking. Methods: The DLQI was completed by adult patients attending a dermatology secondary-care clinic as they arrived at their appointment and given to the clinician. Clinicians recorded whether the DLQI information was used and whether it influenced treatment decision-making.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…It has been shown that quality of life instruments are beneficial in routine clinical practice [23]. Our work shows that the use of Skindex-29 can help dermatologists to identify non-adherent acne patients.…”
Section: Discussionmentioning
confidence: 81%
“…It has been shown that quality of life instruments are beneficial in routine clinical practice [23]. Our work shows that the use of Skindex-29 can help dermatologists to identify non-adherent acne patients.…”
Section: Discussionmentioning
confidence: 81%
“…DLQI data showed an enhanced quality of life after augmentation. Although the DLQI has proven to be an effective tool for clinical routine and randomized trials, it has not been specifically used for facial lipoatrophy before and therefore comparison with other study results is not possible [5, 6,26,27,28]. The decision to utilize this questionnaire was based on positive experiences in our department for evaluating quality of life in a variety of skin disorders such as psoriasis, acne and atopic dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…The objective measurement of treatment outcomes is hugely important for the implementation and subsequent evaluation of guideline-compliant care [40, 41]. As part of the ‘PsoMetrics’ project series, a uniform national system of determining outcomes in psoriasis has now been started.…”
Section: Further Plans To Improve the Quality Of Psoriasis Carementioning
confidence: 99%